2020
DOI: 10.1080/21655979.2020.1795384
|View full text |Cite
|
Sign up to set email alerts
|

The role of long intergenic noncoding RNA 00511 in malignant tumors: a meta-analysis, database validation and review

Abstract: Increasing studies suggested that long intergenic noncoding RNA 00511 (LINC00511) could facilitate the progression of various malignancies and correlates with prognosis of patients with malignant tumors. However, its clinical significance is still not completely clarified. Therefore, we performed a meta-analysis and bioinformatics analysis to further evaluate the correlation of LINC00511 expression level with prognosis and metastasis in patients with tumors. The pooled hazard ratio (HR) with 95% confidence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Advanced tumors are often malignant, prone to relapse after treatment and have poor prognosis. Many diagnostic and prognostic markers have been applied to cancers, but the results may be not satisfactory [ 33–35 ]. Thus, it is important to identify more effective prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced tumors are often malignant, prone to relapse after treatment and have poor prognosis. Many diagnostic and prognostic markers have been applied to cancers, but the results may be not satisfactory [ 33–35 ]. Thus, it is important to identify more effective prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…The Q statistic and I 2 was used to test and quantify heterogeneity. The random effect model is chosen to calculate the pooled SMD with 95% CI, when the p value of the Cochrane Q test was <0.05 or I 2 is ≥50% [ 30 , 31 ]. Otherwise, the random effect model was used.…”
Section: Methodsmentioning
confidence: 99%
“…Otherwise, the random effect model was used. Sensitivity analyses were performed by omitting a single study in each step [ 30 , 31 ]. Subgroup analyses were conducted by age, country, and the definition of severe GI involvements.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, lncRNAs are a major class of RNA molecules which exert a powerful effect on various physiological and pathological processes involving in tumor growth, progression, and prognosis. In addition, lncRNAs could provide potential clues for developing novel therapeutic approaches for cancers [8]. Previous studies have found that lncRNA HOX antisense intergenic (HOTAIR) is significantly increased in cancerous tissues in comparison to normal tissues in gastric cancer, urothelial cell carcinoma and renal cell carcinoma [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lncRNAs could provide potential clues for developing novel therapeutic approaches for cancers [8]. Previous studies have found that lncRNA HOX antisense intergenic (HOTAIR) is significantly increased in cancerous tissues in comparison to normal tissues in gastric cancer, urothelial cell carcinoma and renal cell carcinoma [8][9][10]. Additionally, lncRNA HOTAIR is closely related to cell proliferation and migration ability [10].…”
Section: Introductionmentioning
confidence: 99%